Targeting Parthanatos in Ischemic Stroke - Koehler, Raymond C.; Dawson, Valina L.; Dawson, Ted M. (Frontiers in Neurology, 2021)
Parthanatos is a cell death signaling pathway in which excessive oxidative damage to DNA leads to over-activation of poly(ADP-ribose) polymerase (PARP). PARP then generates the formation of large poly(ADP-ribose) polymers that induce the release of apoptosis-inducing factor from the outer mitochondrial membrane. In the cytosol, apoptosis-inducing factor forms a complex with macrophage migration inhibitory factor that translocates into the nucleus where it degrades DNA and produces cell death. In a review of the literature, we identified 24 publications from 13 laboratories that support a role for parthanatos in young male mice and rats subjected to transient and permanent middle cerebral artery occlusion (MCAO). Investigators base their conclusions on the use of nine different PARP inhibitors (19 studies) or PARP1-null mice (7 studies). Several studies indicate a therapeutic window of 4–6 h after MCAO. In young female rats, two studies using two different PARP inhibitors from two labs support a role for parthanatos, whereas two studies from one lab do not support a role in young female PARP1-null mice. In addition to parthanatos, a body of literature indicates that PARP inhibitors can reduce neuroinflammation by interfering with NF-κB transcription, suppressing matrix metaloproteinase-9 release, and limiting blood-brain barrier damage and hemorrhagic transformation. Overall, most of the literature strongly supports the scientific premise that a PARP inhibitor is neuroprotective, even when most did not report behavior outcomes or address the issue of randomization and treatment concealment. Several third-generation PARP inhibitors entered clinical oncology trials without major adverse effects and could be repurposed for stroke. Evaluation in aged animals or animals with comorbidities will be important before moving into clinical stroke trials.